Cancer incidence and metolachlor use in the Agricultural Health Study: An update. Issue 11 (25th June 2015) - Silver, Sharon R.; Bertke, Steven J.; Hines, Cynthia J.; Alavanja, Michael C.R.; Hoppin, Jane A.; Lubin, Jay H.; Rusiecki, Jennifer A.; Sandler, Dale P.; Beane Freeman, Laura E.
Abstract : Metolachlor, a widely used herbicide, is classified as a Group C carcinogen by the U.S. Environmental Protection Agency based on increased liver neoplasms in female rats. Epidemiologic studies of the health effects of metolachlor have been limited. The Agricultural Health Study (AHS) is a prospective cohort study including licensed private and commercial pesticide applicators in Iowa and North Carolina enrolled 1993–1997. We evaluated cancer incidence through 2010/2011 (NC/IA) for 49, 616 applicators, 53% of whom reported ever using metolachlor. We used Poisson regression to evaluate relations between two metrics of metolachlor use (lifetime days, intensity‐weighted lifetime days) and cancer incidence. We saw no association between metolachlor use and incidence of all cancers combined ( n = 5, 701 with a 5‐year lag) or most site‐specific cancers. For liver cancer, in analyses restricted to exposed workers, elevations observed at higher categories of use were not statistically significant. However, trends for both lifetime and intensity‐weighted lifetime days of metolachor use were positive and statistically significant with an unexposed reference group. A similar pattern was observed for follicular cell lymphoma, but no other lymphoma subtypes. An earlier suggestion of increased lung cancer risk at high levels of metolachlor use in this cohort was not confirmed in this update. This suggestion of an association between metolachlor and liver cancer among pesticide applicators is a novel finding and echoes observation of increased liver neoplasms in some animal studies. However, our findings for both liver cancer and follicular cell lymphoma warrant follow‐up to better differentiate effects of metolachlor use from other factors. Abstract : What's new? Metolachlor, a widely used herbicide, has been classified as a possible human carcinogen (Group C) by the U.S. Environmental Protection Agency based on an increase in liver neoplasms in female rats. This update of pesticide applicators in the Agricultural Health Study is the first occupational epidemiology assessment to report positive associations between metolachlor use and liver cancer in humans. For both liver cancer and follicular cell lymphoma, lifetime and intensity‐weighted lifetime days of metolachor use showed positive trends that were statistically significant when applicators with no metolachlor use were used as the referent group.